ZnO micro/nanocrystals grown by Laser Assisted Flow Deposition - Rodrigues, J. (2017)
Laser assisted flow deposition (LAFD) is a very high yield method based on a vapor-solid mechanism, allowing the production of ZnO crystals in a very short time. The LAFD was used in the growth of different morphologies (nanoparticles, tetrapods and microrods) of ZnO micro/nanocrystals and their microstructural characterization confirms the excellent crystallinity of the wurtzite structure. The optical properties of the as-grown ZnO crystals investigated by low temperature photoluminescence (PL) evidence a well-structured near band edge emission (NBE) due to the recombination of free (FX), surface (SX) and donor bound ((DX)-X-0) excitons. Among the most representative emission lines, the 3.31 eV transition was found to occur in the stacking faults-free microrods. The luminescence behavior observed in H passivated samples suggests a closer relationship between this optical center and the presence of surface states. Besides the unintentionally doped micro/nanocrystals, ZnO/Ag and ZnO/carbon nanotubes (CNT) hybrid structures were processed by LAFD. The former aims at the incorporation of silver as a p-type dopant and the latter envisaging photovoltaic applications. Silver-related spherical particles were found to be inhomogeneously distributed at the microrods surface, accumulating at the rods tips and promoting the ZnO nanorods re-nucleation. Despite the fact that energy dispersive X-ray measurements suggest that a fraction of the silver could be incorporated in the ZnO rods, no new related luminescence lines or bands were observed when compared with the as-grown samples. For the case of the ZnO/CNT composites two main approaches were adopted: i) a direct deposition of ZnO particles on the surface of vertically aligned multi-walled carbon nanotubes (VACNTs) forests without employing any additional catalyst and ii) new ZnO/CNT hybrids were developed as bucky paper nanocomposites. The use of the LAFD technique in the first approach preserves the CNTs structure and alignment and avoids the collapse of the VACNTs array, which is a major advantage of this method. On the other hand, LAFD grown ZnO nanoparticles and tetrapods were used to produce ZnO/CNT buckypaper nanocomposites. When compared with the as-grown samples the PL spectra of the composites structures behave differently. For the case of the ZnO/VACNTs no changes on the peak position and spectral shape were observed. Only an enhancement of the overall luminescence was found to occur. On contrary, for the buckypaper nanocomposites notable changes on the spectral shape and peak position were observed, likely due to distinct surface band bending effects for the ZnO nanoparticles and tetrapods embedded in the CNTs.